Teachers' understanding of critical language awareness and their enactment of this understanding in the classroom - Petersen, Lucia (School of Education, 2014)
This study was prompted by my role as Afrikaans Curriculum Advisor which is inter alia to identify and address shortcomings and needs in the professional development of teachers. One of my immediate interventions was to help teachers understand critical literacy in order to implement Critical Language Awareness (CLA) as defined in the newly revised CAPS curriculum. Teachers need to master teaching CLA before its implementation in terms of the curriculum, introduced incrementally in 2012 in Grade 10. In order to determine teachers' understanding of CLA I selected three Afrikaans Lead Teachers who attended most of the sessions presented as part of the Grade 10 and 11 CAPS orientation. The research question therefore looks at selected teachers' understanding of CLA and their enactment of this understanding in the classroom. The theoretical framework for the study draws on Critical Discourse Analysis (CDA) which views language not only as a form of social practice, but as a socially conditioned and conditioning process. (Fairclough, 2001, p. 19). The data collected for the three case studies were audio taped individual interviews with each teacher to probe their personal understanding of CLA, as well as video recorded complete lessons of CLA taught by each teacher. For my data analysis I drew on Fairclough's model for CDA as interpreted by Janks (1997). Analysis revealed how two of the teachers approached texts as though meaning is singular, and the third constructed meaning as multiple. Teachers' approaches to meaning in text were found to either close down or open up opportunities for critical class discussion. Another significant finding is how teachers' identities and personal histories impacted on their selection of texts for the critical literacy lesson, and their pedagogies. I explore how these pedagogies restricted/enabled classroom interaction. An implication for teacher education is that teachers should not only be trained in content and pedagogy, but should be made aware of and assisted in dealing with their own identity issues which might emerge while teaching critical literacy.